Analisis Faktor Yang Dipertimbangkan Pasien Dalam Mempersepsikan Mutu Pelayanan Di Rsia Muslimat Jombang - Aslichah, Hj; Susanti, Hevi (eBA Journal: Journal Economics, Bussines and Accounting, 2016)
The purpose of this study was to determine whether the physical factors significantly(Tangible), factor reliability (Reliability), factor responsiveness (Responsiveness),factors of service (service),factor empathy(Empathy) into consideration a patient in perceiving the quality of service in RSIA Muslimat Jombang addition quality / service quality. By using the calculation factor analysis techniques Principal Component Analysis (PCA) and varimax rotation can conclude the cumulative percentage of variance showed a value of 63.6%. This means that the factors that exist in these calculations is able to explain the factors into consideration patient in perceiving the quality of service in RSIA's Women Jombang. Furthermore, and 20 items were analyzed on the basis of the magnitude elgenvalue> l can be simplified into 8 percentage variian factor in the order as follows: (i) factors support RSIA's Women Jombang and needs of the patients (14.3%), (2) understand the factors patients (10.2%), (3) factors communications (8.0%), (4) good relationship factors (7.3%), (5) the trust factor (6.9%), (6) the accuracy factor services (6.2%), (7) a reliability factor of service personnel (5.5%), (8) the physical reality factor (5.3).